Involvement of Oxidative Stress and the Epidermal Growth Factor Receptor in Diesel Exhaust Particle-Induced Expression of Inflammatory Mediators in Human Mononuclear Cells - Li, Fangfang; An, Zhen; Li, Haibin; Gao, Xia; Wang, Gui; Wu, Weidong (Mediators of Inflammation, 2019)
Exposure to diesel exhaust particles (DEPs) has been associated with increased incidence of cardiopulmonary diseases. This study is aimed at examining the proinflammatory effects of DEP on primary human peripheral blood mononuclear cells (PBMC) and the underlying mechanisms using a human mononuclear cell line, THP-1. DEPs were incubated with the PBMC and THP-1 cells for 24 h, respectively. The supernatants were collected and subjected to measurement of proinflammatory mediators including interleukin 8 (IL-8) or tumor necrosis factor α (TNFα) by ELISA. Levels of reactive oxygen species (ROS) were determined using flow cytometry. Phosphorylation of the epidermal growth factor receptor (EGFR) was examined with immunoblotting. Exposure to DEP induced a concentration-dependent increase in the expression of IL-8 and TNFα in the PBMC and THP-1 cells. Further mechanistic studies with THP-1 cells indicated that DEP stimulation increased intracellular levels of ROS, an indicator of oxidative stress, and phosphorylation of the EGFR, indicative of EGFR activation. Pretreatment of THP-1 cells with the antioxidant N-acetyl-L-cysteine (NAC) markedly blunted DEP-induced EGFR phosphorylation, indicating that oxidative stress was involved in DEP-induced EGFR activation. Furthermore, the pretreatment of THP-1 cells with either NAC or a selective EGFR inhibitor significantly blocked DEP-induced IL-8 expression, implying that oxidative stress and subsequent EGFR activation mediated DEP-induced inflammatory response. In summary, DEP stimulation increases the expression of proinflammatory mediators in human mononuclear cells, which is regulated by oxidative stress-EGFR signaling pathway.